Meta-analysis of the effect of sophora flavescens on tumor metastasis-induced bone neuropathic pain - Cheng Chang; Di Sun; Zhilei Zhang; Lei He; Qiang Wang; Yingchao Shen; Hengzhou Zhu; Donghua Fan (Frontiers Media S.A., 2024)
BackgroundTumor metastasis to bone is a critical and painful stage in cancer progression, significantly affecting patients' quality of life. Traditional treatments for bone neuropathic pain often exhibit limited efficacy and undesirable side effects. Sophora flavescens, an herb used in traditional Chinese medicine, has shown potential analgesic and anti-cancer properties, but the existing evidence is fragmented and inconsistent.MethodsIn accordance with PRISMA guidelines, an extensive literature search was performed across PubMed, Web of Science, and Cochrane Library databases, Embase, Medline, CNKI, VIP, Wanfang Database, CBMdisc to identify relevant studies. The inclusion criteria focused on randomized controlled trials (RCTs) investigating the use of Sophora flavescens for bone neuropathic pain. Data related to pain intensity, mechanisms of action, and safety were extracted and analyzed using meta-analysis techniques. The quality of the studies was assessed using the Cochrane Risk of Bias tool.ResultsSeven studies met the inclusion criteria, involving a total of 463 patients with bone neuropathic pain induced by tumor metastasis. The meta-analysis revealed a significant overall reduction in pain intensity for patients treated with Sophora flavescens compared to control groups (mean difference = 26.45, 95% CI: 13.89, 39.00, P < 0.0001). Specifically, the Karnofsky Performance Status (KPS) increase rate showed a combined risk ratio of 1.62 (95% CI: 1.32, 1.99, P < 0.0001), indicating improved performance status with treatment. Pain scores also significantly decreased (mean difference = 26.45, 95% CI: 13.89, 39.00, P < 0.0001) despite substantial heterogeneity among studies (I2 = 91%). Funnel plots suggested minimal publication bias, and sensitivity analyses confirmed the stability of these results. The included studies reported minimal adverse effects, indicating good tolerability of Sophora flavescens.ConclusionSophora flavescens demonstrates significant potential as an adjunctive therapy for managing bone neuropathic pain induced by tumor metastasis, offering substantial pain relief with minimal adverse effects.